Postoperative Complications of Septal Quilting and BIPP Packing following Septoplasty - Thapa, N; Pradhan, B (Journal of Nepal Health Research Council, 2011)
Background: Septoplasty is one of the most common surgeries in otorhinolaryngology. After septal surgery nasal packing is usually done to prevent complications like haemorrhage, septalhaematoma. However it is associated with many postoperative complications such as pain, hypoxia, dryness in throat, headache, epiphora, vestibular stenosis, crusting, synaechiae, secondary infection etc. In order to prevent these complications quilting has been developed. No study has been done in our country to comparethe postoperative complications after septoplasty. Methods: This study was carried outto compare postoperative crusting, oedema, synaechiaand infection in patients who underwent septal quilting and BIPP packing following septoplastyfrom August 2008 to July 2011 in the Department of ENT-Head and Neck Surgery, Tribhuvan University Teaching Hospital, Maharajgunj, Kathmandu, Nepal. Results: There were 44 patientsin quilting and 41 patients in BIPP packing group. Out of 44 patients of quilting group, crusting occurred in 3 patients, oedema in 4 patients, synechia in 1 patient and infection in 3 patients.Out of 41 patients of BIPP packing group,9 patients had crusting,oedema was present in 7 patients, 6 patients had synaechia and 5 patients had infection. Crusting and synaechia was found to be statistically significant while oedema and infection was not significant between two groups. Conclusions: Complications like excessive crusting, oedema, synaechia and infection can be minimized by quilting suture following septoplasty. Keywords: BIPP packing, crusting, infection, oedema, quilting, suture, synaechia, septoplasty.